International Solidarity Fund - TUC poster, 1957 (1957)
1957 1945-1960 "International Solidarity Fund - TUC poster, 1957" [T0370.jpg], 1957 In 1957, the International Confederation of Free Trade Unions (ICFTU) re-established the International Solidarity Fund to collect funds for emergency relief in disasters, helping victims of oppression, strengthening trade unions and aid to developing countries. During its first year, aid was distributed to a wide range of organisations e.g. victims of mine disasters in India and Korea, support for families of trade unionists in Cyprus and defence costs in the South African treason trials.